The Yeast Retrograde Response as a Model of Intracellular Signaling of Mitochondrial Dysfunction - Jazwinski, S. Michal; Kriete, Andres (Frontiers in Physiology, 2012)
Mitochondrial dysfunction activates intracellular signaling pathways that impact yeast longevity, and the best known of these pathways is the retrograde response. More recently, similar responses have been discerned in other systems, from invertebrates to human cells. However, the identity of the signal transducers is either unknown or apparently diverse, contrasting with the well-established signaling module of the yeast retrograde response. On the other hand, it has become equally clear that several other pathways and processes interact with the retrograde response, embedding it in a network responsive to a variety of cellular states. An examination of this network supports the notion that the master regulator NFkB aggregated a variety of mitochondria-related cellular responses at some point in evolution and has become the retrograde transcription factor. This has significant consequences for how we view some of the deficits associated with aging, such as inflammation. The support for NFkB as the retrograde response transcription factor is not only based on functional analyses. It is bolstered by the fact that NFkB can regulate Myc-Max, which is activated in human cells with dysfunctional mitochondria and impacts cellular metabolism. Myc-Max is homologous to the yeast retrograde response transcription factor Rtg1-Rtg3. Further research will be needed to disentangle the pro-aging from the anti-aging effects of NFkB. Interestingly, this is also a challenge for the complete understanding of the yeast retrograde response.